2021
DOI: 10.1371/journal.pgen.1009527
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a gustatory receptor tuned to sinigrin in the cabbage butterfly Pieris rapae

Abstract: Glucosinolates are token stimuli in host selection of many crucifer specialist insects, but the underlying molecular basis for host selection in these insects remains enigmatic. Using a combination of behavioral, electrophysiological, and molecular methods, we investigate glucosinolate receptors in the cabbage butterfly Pieris rapae. Sinigrin, as a potent feeding stimulant, elicited activity in larval maxillary lateral sensilla styloconica, as well as in adult medial tarsal sensilla. Two P. rapae gustatory rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 76 publications
1
40
0
Order By: Relevance
“…Recently, more research has been focused on the function of three chemosensory receptor types: ORs, GRs, and IRs ( Zhang R.B. et al, 2017 ; Yang et al, 2020 , 2021 ). In this study, we identified six ORs in the A. spiniferus transcriptome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, more research has been focused on the function of three chemosensory receptor types: ORs, GRs, and IRs ( Zhang R.B. et al, 2017 ; Yang et al, 2020 , 2021 ). In this study, we identified six ORs in the A. spiniferus transcriptome.…”
Section: Discussionmentioning
confidence: 99%
“…In M. persicae , the high glutamine concentration stimulated the feeding behavior ( Cao et al, 2017 ). Overexpressing PrapGR28 from Pieris rapae in Drosophila files resulted in a strong preference to the food with sinigrin whereas the wild-type (WT) files showed avoidance ( Yang et al, 2021 ). In B. mori , BmorGR66 mutant showed no significant feeding preference for both mulberry leaves and Mongolian oak leaves, while WT B. mori did not eat Mongolian oak leaves ( Zhang Z.J.…”
Section: Discussionmentioning
confidence: 99%
“…Grs in insects are known to form heterodimers with co-receptors to recognize the tastant (Dahanukar et al ., 2007; Lee et al ., 2009). Nevertheless, there are several instances of the expression of a single insect Gr in a heterologous expression system sufficient to confer tastant responses, including Gr5a, Gr43a and Gr64e from Drosophila , BmGr8 and BmGr9 from the silkworm Bombyx mori , PxutGr1 from the swallowtail butterfly Papilio xuthus , HarmGR35, HarmGR50 and HarmGR195 from the polyphagous pest Helicoverpa armigera , AgGr25 from the malaria mosquito Anopheles gambiae (Chyb et al ., 2003; Freeman et al ., 2014; Sato et al , 2011; Zhang et al ., 2011; Ozaki et al ., 2011; Xu et al ., 2016), and PrapGr28 from the cabbage butterfly Pieris rapae (Yang et al ., 2021). In this study, the HEK293T cells expressing NlGr23a caused responses to OA (Figure 1F).…”
Section: Discussionmentioning
confidence: 99%
“…The lepidopteran Gr phylogeny was generated using full-length amino acid sequences of Grs from Bombyx mori [30], P. xylostella [38], H. melpomene [39], PxutGr1 [23], and PrapGr28 [24]. The sequences were aligned with MAFFT v.7 (http://mafft.cbrc.jp/alignment/server/).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…PxutGr1 from the swallowtail butterfly, Papilio xuthus , is responsible for the sensitivity of tarsal taste sensilla to synephrine, which acts as an ovipositioning stimulant [23]. PrapGr28 from the cabbage butterfly, Pieris rapae , contributes to sinigrin sensitivity in adult tarsal taste sensilla [24], although sinigrin is a feeding stimulant for their larvae [25]. PxylGr34 from the diamondback moth, Plutella xylostella , is involved in response to canonical plant hormones, brassinolide, and 24-epibrassinolide, a feeding and oviposition deterrent, in MG of larvae [26].…”
Section: Introductionmentioning
confidence: 99%